การพัฒนาการศึกษาในยุคดิจิทัลตามกระบวนทัศน์ทางการศึกษาตาม มาตรฐานคุณวุฒิระดับอุดมศึกษา พ.ศ. 2565 - คำคง, เสริมศักดิ์; บุญญประดับกุล, กำธร; ทองใบ, จิรัชญา (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 1 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 1 : มกราคม - เมษายน 2567, 2024)
The education is considered highly important for personal development and serves as the foundation for other forms of development. Regardless of the aspect of development, it must always commence with human development. Human development can be achieved through various means, and thus, the progress of a country should be parallel to the advancement of its people. Education, therefore, plays a crucial role in this regard. The Thai qualifications framework for higher education (TQF: HEd) is a comprehensive framework that outlines the country's higher education qualification system. It encompasses qualifications, subject divisions, and a seamless progression from one qualification level to a higher one. It also establishes standards of learning outcomes that increase in line with the level of qualification. To keep up with the changing landscape, a new educational conceptual framework is required to align concepts, values, and practices within the education system with consumerism. The current consumerist approach to education fails to foster learners' ability to invent and develop new ideas for themselves and society during the teaching and learning process. Teachers merely transmit knowledge to students, resulting in a culture of knowledge consumption. Consequently, creativity is lacking. In order to provide valuable education to students and society in a creative manner, beneficial to the country's development, a shift in education and the production and development of Thai teachers towards creative productivity is necessary. Teacher education institutions must integrate technology and information relevant to the digital age, utilizing them as tools to produce and develop teachers with the knowledge and skills to effectively manage teaching and create educational innovations.